Pendekatan Pembelajaran Seni Berbasis Ecoprint untuk Meningkatkan Kreatif Thinking Anak Usia Dini - Arofah, Arofah; Pradana, Pascalian Hadi; Suwargono, Trio (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the application of an ecoprint-based art learning approach to improving creative thinking skills in early childhood. The method used in this study was Classroom Action Research (CAR), based on the Kemmis and McTaggart model, which consists of three cycles: pre-cycle, Cycle I, and Cycle II. The results showed a significant increase in children's creativity indicators, namely fluency, flexibility, originality, and elaboration. The classical average for the indicators in the pre-cycle activities was only 20.46%. In cycle I, it increased to 47.73%, and in cycle II, it increased again to 86.36%. The conclusion is that an ecoprint-based art learning approach can enhance creative thinking in early childhood. Keywords: Early Childhood, Creative Thinking, Ecoprint, Art Learning